2018
DOI: 10.1007/s11274-018-2465-0
|View full text |Cite
|
Sign up to set email alerts
|

Mutational analyses of regulatory genes, mexR, nalC, nalD and mexZ of mexAB-oprM and mexXY operons, in efflux pump hyperexpressing multidrug-resistant clinical isolates of Pseudomonas aeruginosa

Abstract: The present study deals with membrane-bound efflux pumps, MexAB-OprM and MexXY and their respective regulatory genes mexR, nalC, nalD and mexZ in multidrug resistant (MDR) Pseudomonas aeruginosa. Following antibiotic sensitivity testing and detection of various beta-lactamases, hyperexpression of efflux pump genes, mexB and mexY in the isolates was investigated using semi-quantitative and real-time reverse transcription-PCR. Amplicons from regulatory genes were sequenced and subjected to mutational and phyloge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
40
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(43 citation statements)
references
References 49 publications
0
40
1
Order By: Relevance
“…The contribution of the MexAB-OprM e ux pump to the resistance of P. aeruginosa strains was evident, as 17 out of 19 statistically signi cant mutations associated with MexAB-OprM e ux pump activity also correlated with resistance of the studied strains (p < 0.05). Some authors suggest that mutations in the mexR, nalC, and nalD genes can impair their function, favoring MexAB-OprM e ux pump overexpression with a consequent increase in bacterial resistance [6,12,13], however, in our study, same haplotypes (mutations) lead to different MexAB-OprM e ux pump phenotypic behavior and resistance.…”
Section: Discussioncontrasting
confidence: 61%
See 2 more Smart Citations
“…The contribution of the MexAB-OprM e ux pump to the resistance of P. aeruginosa strains was evident, as 17 out of 19 statistically signi cant mutations associated with MexAB-OprM e ux pump activity also correlated with resistance of the studied strains (p < 0.05). Some authors suggest that mutations in the mexR, nalC, and nalD genes can impair their function, favoring MexAB-OprM e ux pump overexpression with a consequent increase in bacterial resistance [6,12,13], however, in our study, same haplotypes (mutations) lead to different MexAB-OprM e ux pump phenotypic behavior and resistance.…”
Section: Discussioncontrasting
confidence: 61%
“…Ozer et al, (2012) reported a consistent positive correlation between MexAB-OprM expression and multidrug resistance in 50 P. aeruginosa clinical strains [46]. However, in our study, of the P. aeruginosa strains that showed MexAB-OprM activity (phenotypic positive-strains), only in 52.9% the MexAB-OprM e ux pump was the most likely cause of resistance (+), in the remaining 47% of the strains the MexAB-OprM e ux pump was contributing to the resistance (*), which demonstrated that although the MexAB-OprM pump shows positive activity and contributes to resistance, this is not the only mechanism of resistance in these strains [13]. For example, in the remaining phenotypic negative-strains (n = 40) (3 S, 14 MDR, 16 XDR and 7 PDR), where the MexAB-OprM e ux pump was unlikely to be the cause of the resistance (Table 1); the high-drug resistance can be attributed in part to the production of carbapenemases (1 MDR, 3 XDR, and 2 PDR: serine carbapenemases, 8 XDR: metallo-.βlactamases).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Semi-quantitative RT-PCR using primers (Eurofins Genomics India Pvt. Ltd., Bangalore) for genes such as rpsL and mexD [5] [6] were performed as described by us in a related study [7]. The RT-PCR reactions were performed using a mi-…”
Section: Semi-quantitative Rt-pcrmentioning
confidence: 99%
“…The regulatory nfxB gene primer [8] was used for DNA amplifications and sequencing [7]. The ampliconic sequences were analyzed with NCBI BLAST tool (https://www.ncbi.nlm.nih.gov/) by comparison with sequences of the reference strain, P. aeruginosa PAO1, retrieved from the GenBank database.…”
Section: Pcr Amplification and Sequencing Of The Nfxb Gene And Its Phmentioning
confidence: 99%